High-wiping-property antistatic dust-free cloth and preparation method thereof
Through the design of modified composite materials of seaweed fibers and ultrafine viscose fibers and anti-static fluids, the poor hydrophilicity, poor anti-bacteriality and electrostatic problems of traditional dust-free cloth are solved, and the high cleanliness and anti-static properties are improved. , suitable for occasions with high cleanliness requirements and reduces production costs.
Patent Information
- Application Number
- CN202411216612.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2024-12-13
AI Technical Summary
Traditional dust-free cloth has defects such as poor hydrophilicity, poor antibacteriality, electrostatic problems, non-reusability, high production costs and environmental pollution in clean environments, and it is difficult to meet the needs of high cleanliness and large-scale production.
Using a composite material of modified seaweed fiber and ultrafine viscose fiber, it is designed through plasma treatment and nanosilica sol impregnation, combining antibacterial and antistatic fluids, including methacrylic acid, polyvinyl alcohol, methacrylamide, acrylic acid Dimethylaminoethyl ester, antistatic agent, antibacterial agent, surfactant and initiator are carried out, and hydrospinning treatment and drying processes are carried out to prepare a highly wipeable antistatic dust-free cloth.
It has achieved high cleanliness, antibacterial properties, antistatic properties, water and oil absorption and softness, reduced production costs, is suitable for large-scale production, and maintains excellent performance under low humidity conditions.
Smart Images

Figure BDA0005021703500000091 
Figure BDA0005021703500000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of dust-free cloths, and in particular to a high-wiping antistatic dust-free cloth and a preparation method thereof. Background Art
[0002] With the widespread application of clean rooms and the continuous development of pollution control technology in the clean room industry, the use of clean room consumables is increasing. Among them, dust-free cloth is one of the main clean room consumables. Its main function is to remove pollution sources in products, production equipment and clean rooms. The traditional dust-free cloth substrate is mainly woven by chemical fiber filaments such as polyester, nylon or composite yarn through textile equipment. The main advantage of chemical fiber filaments is that the particles adsorbed on the surface of the filaments can be removed during the ultra-clean cleaning process, and the cleanliness of the dust-free cloth produced is relatively high. However, woven cloths made of chemical fiber filaments have many disadvantages: 1. Poor hydrophilicity and antibacterial properties, so the ability to remove liquid pollution sources is poor and it is easy to breed bacteria. It can only be used once and is difficult to reuse. Chemical fiber filaments are naturally non-degradable. The greater the consumption, the greater the pollution to the environment; 2. When used under dry conditions, it is easy to generate static voltage, which harms the product; 3. The gram weight is large, and there are many processes in the weaving process. Compared with non-woven fabrics, the production cost is relatively high. Summary of the invention
[0003] The purpose of this application is to provide a high-wiping antistatic dust-free cloth and a preparation method thereof in view of the deficiencies of the current technology. The high-wiping antistatic dust-free cloth of the present application has excellent antibacterial properties, good and durable antistatic properties, high cleanliness, good softness, and is not easy to shed hair and powder. It has high water and oil absorption and excellent ability to clean the surface of objects. At the same time, the preparation method of the present application is simple and efficient, and is suitable for large-scale production.
[0004] In a first aspect, the present application provides a method for preparing an antistatic dust-free cloth with high wiping performance, adopting the following technical scheme: A method for preparing an antistatic dust-free cloth with high wiping performance, comprising the following steps: S1. Pre-spinning opening: feeding the composite fiber into a bale opener for opening and fine opening, so that the compacted fiber blocks in the composite fiber are loosened into small fiber bundles through mechanical impact and tearing, and then fully mixed in a mixing box to obtain a mixture A; S2, combing and laying: putting the mixed material A into a carding machine for combing, conveying the combed composite fiber to a laying machine for laying, and then forming a fiber cloth through a drafting machine to obtain a fiber cloth; S3, hydroentanglement treatment: conveying the fiber cloth to a hydroentanglement machine and hydroentanglement treatment with 25 MPa high-pressure water to obtain a hydroentangled cloth; S4, pre-drying: squeeze the spunlace cloth to dry the water, and then send it into the dryer for pre-drying to obtain dust-free cloth; S5, dip-coating with antibacterial and antistatic liquid: immerse the dust-free cloth in the antibacterial and antistatic liquid, accurately control the immersion time to be 30-33 seconds, and obtain the dust-free cloth dipped in the antibacterial and antistatic liquid; wherein, the antibacterial and antistatic liquid, in terms of weight parts, is prepared from the following raw materials: 68-72 parts of methacrylic acid, 0.4-0.6 parts of polyvinyl alcohol, 4.5-5.5 parts of methacrylamide, 4.5-5.5 parts of dimethylaminoethyl acrylate, 3-5 parts of antistatic agent, 1-1.2 parts of antibacterial agent, 1-1.3 parts of surfactant, 3-5 parts of allyl polyoxyethylene ether, 2.4-2.6 parts of initiator aqueous solution, and 395-400 parts of deionized water; S6, drying and winding: drying the dust-free cloth dipped in the antibacterial and antistatic liquid at a temperature of 150-160° C. for 80-90 seconds, winding it, and cutting it to obtain a highly wiping antistatic dust-free cloth; The composite fiber is composed of modified seaweed fiber and ultrafine viscose fiber in a mass ratio of 1:9.
[0005] By adopting the above technical scheme, the high-wiping antistatic dust-free cloth of the present application achieves excellent performance through a specific preparation method and ingredient selection. The composite use of modified seaweed fiber and ultrafine viscose fiber not only improves the water and oil absorption and cleaning ability of the dust-free cloth, but also increases the softness and non-linting and powder-removing characteristics of the dust-free cloth. The modified seaweed fiber is treated with plasma and impregnated with nano-silica sol to improve thermal stability and spinnability, and enhance the binding force with other raw materials. The formula design of the antibacterial antistatic liquid takes into account many aspects of performance improvement. Ingredients such as methacrylic acid, polyvinyl alcohol, methacrylamide, and dimethylaminoethyl acrylate provide good film-forming properties and adhesion. The addition of antibacterial agents ensures that the dust-free cloth has long-lasting and stable antibacterial properties. The antistatic agent forms an effective conductive network structure, which can maintain a low resistivity even under low humidity conditions, and achieve excellent antistatic effects. The addition of surfactants improves the fluidity of the antibacterial antistatic liquid, promotes its penetration into the non-woven fabric, and forms a mesh structure, thereby significantly improving the comprehensive performance of the dust-free cloth. The addition of allyl polyoxyethylene ether improves the softness of the chemical adhesive layer, making the dust-free cloth more pliable during use and reducing damage to the surface of the cleaned object. The use of an initiator aqueous solution ensures the uniform coating of the antibacterial and antistatic liquid on the dust-free cloth, further improving the performance stability of the dust-free cloth. The precise control of the pre-baking and drying steps not only ensures the dryness of the dust-free cloth, but also helps to fix the antibacterial and antistatic liquid on the dust-free cloth, ensuring the performance stability of the dust-free cloth during use. The entire preparation process is simple and efficient, suitable for large-scale production, and is conducive to reducing production costs and improving production efficiency. In summary, the high-wiping antistatic dust-free cloth of the present application has achieved a comprehensive improvement in antibacterial performance, antistatic performance, water and oil absorption, and cleaning ability through careful raw material selection and preparation process, while maintaining the softness of the dust-free cloth and the characteristics of not easily shedding hair and powder, and is suitable for various occasions with high requirements for cleanliness.
[0006] Preferably, the modified seaweed fiber has a diameter of 2.2 dtex and a length of 38 mm; the ultrafine viscose fiber has a diameter of 0.5 dtex and a length of 45 mm.
[0007] Preferably, the preparation method of the modified seaweed fiber is: treating the seaweed fiber with oxygen plasma at a temperature of 35°C, a vacuum degree of 1000Pa, and a plasma power supply of 500W, then immersing it in nano-silica sol, adding 1.2% of dodecyltrimethylammonium bromide based on the mass of the seaweed fiber, treating for 2-3h, then adding 5-7% of hexachloropropane based on the mass of the seaweed fiber, stirring evenly, washing with deionized water, and drying to obtain the modified seaweed fiber.
[0008] By adopting the above technical scheme, by plasma treatment, the roughness of the surface of the seaweed fiber is improved, the specific surface area of the seaweed fiber is increased, and it is beneficial to improve the wettability of the seaweed fiber. The seaweed fiber is impregnated into the nano-silica sol, and the nano-silica is distributed on the surface of the seaweed fiber, so as to improve the thermal stability of the seaweed fiber and improve the spinnability of the seaweed fiber. Adding dodecyl trimethyl ammonium bromide can improve the adhesion of the nano-silica sol to the seaweed fiber, so as to improve the modification effect. At the same time, adding hexachloropropane can improve the problem of weak bonding between seaweed fiber and other raw materials, and further improve the water and oil absorption of seaweed fiber and the ability to clean the surface of objects. In summary, the modified seaweed fiber prepared by the present application can improve the thermal stability and spinnability of seaweed fiber, improve adhesion and bonding force, so that the dust-free cloth has higher water and oil absorption and excellent ability to clean the surface of objects.
[0009] Preferably, the mass ratio of the seaweed fiber to the nano-silica sol is 5:17-20.
[0010] Preferably, in step S5, the antistatic agent is composed of poly (3,4-ethylenedioxythiophene), octadecyldimethylhydroxyethyl quaternary ammonium nitrate and behenyltrimethylammonium chloride in a mass ratio of 5:3:4.
[0011] By adopting the above technical solution, poly 3,4-ethylenedioxythiophene has conductive properties. When added to the antibacterial and antistatic liquid, the antibacterial and antistatic liquid can have good conductive properties and excellent antistatic effect. The octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate molecule is relatively small and can easily migrate from the inside of the system to the surface. Under certain humidity conditions, its hydrophilic group combines with water through hydrogen bonds to form a conductive channel, which can effectively dissipate static electricity and reduce the surface resistivity of the antibacterial and antistatic layer. The 2-dodecyl trimethyl ammonium chloride molecule is relatively large. It will rely on its unique emulsification properties to be arranged in a directional manner on the surface of the system, and its hydrophilic group will face the external air end, forming a conductive network structure with permeability in the system, which can effectively dissipate static electricity and reduce the surface resistivity of the antibacterial and antistatic layer. By precisely controlling the mass ratio of poly (3,4-ethylenedioxythiophene), octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate and dodecyl trimethyl ammonium chloride to 5:3:4, the antistatic retention time and antistatic effect of the high-wiping antistatic dust-free cloth are made better, and the resistivity is still quite low even under low humidity conditions. This synergistic effect makes the high-wiping antistatic dust-free cloth have better performance in practical applications.
[0012] Preferably, in step S5, the antibacterial agent is a modified graphene-silver composite antibacterial agent.
[0013] Preferably, the preparation method of the modified graphene-silver composite antibacterial agent comprises the following steps: S71. According to the mass fraction, 30 parts of 30 μm thick flake graphite and 200 parts of anhydrous ethanol were mixed, and the solution was mixed evenly by using a variable frequency disperser, and then the mixed solution was poured into a high temperature and high pressure reactor, and the temperature was set to 310°C, the pressure was controlled at 30 MPa, and the speed was 900 r / min. After keeping warm for 40 minutes, the equipment was turned off, the pressure relief valve was opened, and the solution was placed in deionized water at room temperature. When the pressure dropped to 15 MPa, the pressure relief valve was closed, and the product was subjected to ultrasonication, washing, and suction filtration to obtain a filter cake, and the filter cake was freeze-dried for 24 hours and then taken out to obtain graphene; S72, dissolving 25 parts of graphene, 5 parts of silver nitrate and 0.5 parts of sodium hydroxide in 800 parts of deionized water respectively according to their weight parts, stirring evenly, heating to 92° C., keeping the temperature for reaction for 2h-2.5h, washing by centrifugation, spray drying and grinding to obtain a graphene-silver composite antibacterial agent; S73. According to the mass proportions, 25 parts of graphene-silver composite antibacterial agent are placed into 80 parts of 3-aminopropyltrihydroxysilane solution with a mass concentration of 2%, the temperature is raised to 43°C, and the temperature is kept for 8 hours. The mixture is filtered, washed with ethanol for 3 times, and vacuum dried to obtain a modified graphene-silver composite antibacterial agent.
[0014] By adopting the above technical scheme, the prepared graphene-silver composite antibacterial agent has excellent antibacterial properties and can effectively inhibit the growth and reproduction of bacteria. Silver ions have strong antibacterial activity and can destroy the cell wall and cell membrane of bacteria, leading to bacterial death. Graphene has a high specific surface area and good electrical conductivity, which can promote the release and diffusion of silver ions, thereby improving the antibacterial effect. Graphene has good electrical conductivity, which can effectively disperse static charge and reduce surface resistivity, thereby improving antistatic properties. At the same time, the silver ions in the graphene-silver composite antibacterial agent also have a certain electrical conductivity, which can further enhance the antistatic effect. The graphene-silver composite antibacterial agent is modified by 3-aminopropyltrihydroxysilane to improve its dispersibility and compatibility in antibacterial and antistatic liquid. γ-mercaptopropyltrimethoxysilane is used as a coupling agent to enhance the interfacial interaction between the graphene-silver composite antibacterial agent and the dust-free cloth, ensuring that the antibacterial agent can be more evenly distributed on the surface of the dust-free cloth, thereby improving the long-term and stable antibacterial performance of the antistatic dust-free cloth.
[0015] Preferably, in step S5, the surfactant is composed of octadecyltrimethylammonium bromide and polyoxyethylene (10) tridecyl ether in a mass ratio of 4:5.
[0016] By adopting the above technical scheme, octadecyl trimethyl ammonium bromide has good wetting properties, can reduce the contact angle between the liquid and the solid surface, and make the liquid easier to spread on the surface of the non-woven fabric. Polyoxyethylene (10) tridecyl ether can reduce the surface tension of the liquid and further improve the wetting properties. The two work together to make the antibacterial and antistatic liquid easier to penetrate into the non-woven fabric, thereby improving the treatment effect. Both octadecyl trimethyl ammonium bromide and polyoxyethylene (10) tridecyl ether have emulsifying effects, and can evenly mix the oil and water phases in the antibacterial and antistatic liquid to form a stable emulsion. This helps to evenly distribute the antibacterial and antistatic liquid on the non-woven fabric and improve the treatment effect. Polyoxyethylene (10) tridecyl ether has a lower surface tension, which can reduce the interaction force between the liquid and the non-woven fiber, making the antibacterial and antistatic liquid easier to penetrate into the non-woven fabric. At the same time, octadecyl trimethyl ammonium bromide can also reduce the surface tension of the liquid and further improve the permeability. The two work together to make the antibacterial and antistatic liquid penetrate deeper into the non-woven fabric, thereby improving the treatment effect. Both octadecyl trimethyl ammonium bromide and polyoxyethylene (10) tridecyl ether can form a stable micelle structure in the emulsion, preventing the occurrence of emulsion stratification and demulsification. This helps to maintain the stability of the antibacterial and antistatic liquid and ensure that its treatment effect on the non-woven fabric is long-lasting and stable. In summary, the synergistic effect between octadecyl trimethyl ammonium bromide and polyoxyethylene (10) tridecyl ether can improve the wettability, emulsification and permeability of the antibacterial and antistatic liquid, making it easier to penetrate into the non-woven fabric and form a stable emulsion structure, thereby improving the performance of the high-wiping antistatic dust-free cloth.
[0017] Preferably, in step S5, the mass concentration of the initiator aqueous solution is 20%, and the initiator is ammonium persulfate.
[0018] Preferably, in step S5, the preparation method of the antibacterial and antistatic liquid is: deionized water and polyvinyl alcohol are added to a glass reaction kettle according to their mass fractions, high-purity nitrogen is introduced, and the mixture is stirred at a stirring speed of 300-350rpm for 1-1.2h, and then methacrylic acid, methacrylamide, dimethylaminoethyl acrylate, antistatic agent, antibacterial agent, surfactant and allyl polyoxyethylene ether are added in sequence, the temperature is raised to 61-63°C and kept constant; then an initiator aqueous solution is added to initiate the reaction, heating is stopped after the reaction for 8-9h, and the mixture is cooled to room temperature to obtain the antibacterial and antistatic liquid.
[0019] In the second aspect, the present application provides a high-wiping antistatic dust-free cloth, which adopts the following technical solution: As a general technical concept, the present application also provides a high-wiping antistatic dust-free cloth made by the above-mentioned method for preparing a high-wiping antistatic dust-free cloth.
[0020] In summary, the beneficial technical effects of this application are: 1. Excellent antibacterial properties: By adding modified graphene-silver composite antibacterial agent, its dispersibility and compatibility in antibacterial and antistatic liquid are improved, ensuring that the antibacterial agent can be more evenly distributed on the surface of the dust-free cloth, thereby improving the long-term and stable antibacterial performance of the antistatic dust-free cloth.
[0021] 2. Good antistatic performance: By adding conductive materials such as poly 3,4-ethylenedioxythiophene, octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate and docosyl trimethyl ammonium chloride, the high-wiping antistatic dust-free cloth has good conductive properties and excellent antistatic effect, and still has a very low resistivity even under low humidity conditions.
[0022] 3. High cleanliness: The water spunlace treatment and pre-baking process are used to ensure the cleanliness of the dust-free cloth. At the same time, the antibacterial and antistatic liquid is improved by adding surfactants to penetrate the inside of the non-woven fabric to form a mesh structure, thereby improving the comprehensive performance of the dust-free cloth.
[0023] 4. Good softness: Adding allyl polyoxyethylene ether can improve the softness of the chemical adhesive layer, increase the softness of the dust-free cloth, and make it more comfortable and easy to use.
[0024] 5. Simple and efficient preparation method: The preparation method of the present application is simple and efficient, suitable for large-scale production, and is conducive to reducing production costs and improving production efficiency. DETAILED DESCRIPTION
[0025] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0026] In the following Examples and Preparation Examples, 1 part means 10 g.
[0027] Preparation Example 1 Preparation of modified seaweed fiber The preparation method of modified seaweed fiber is as follows: 5 kg of seaweed fiber is treated with oxygen plasma at a temperature of 35°C, a vacuum degree of 1000 Pa, and a plasma power supply of 500 W, and then immersed in 18 kg of nano-silica sol, 0.06 kg of dodecyltrimethylammonium bromide is added, and the treatment is carried out for 2.5 hours, and then 0.3 kg of hexachloropropane is added, stirred evenly, washed with deionized water, and dried to obtain modified seaweed fiber. The diameter of the modified seaweed fiber is 2.2 dtex and the length is 38 mm.
[0028] Preparation Example 2 Preparation of modified graphene-silver composite antibacterial agent The preparation method of the modified graphene-silver composite antibacterial agent comprises the following steps: S71. According to the mass fraction, 30 parts of 30 μm thick flake graphite and 200 parts of anhydrous ethanol were mixed, and the solution was mixed evenly by using a variable frequency disperser, and then the mixed solution was poured into a high temperature and high pressure reactor, and the temperature was set to 310°C, the pressure was controlled at 30 MPa, and the speed was 900 r / min. After keeping warm for 40 minutes, the equipment was turned off, the pressure relief valve was opened, and the solution was placed in deionized water at room temperature. When the pressure dropped to 15 MPa, the pressure relief valve was closed, and the product was subjected to ultrasonication, washing, and suction filtration to obtain a filter cake, and the filter cake was freeze-dried for 24 hours and then taken out to obtain graphene; S72, dissolving 25 parts of graphene, 5 parts of silver nitrate and 0.5 parts of sodium hydroxide in 800 parts of deionized water respectively according to their mass parts, stirring evenly, heating to 92° C., keeping the temperature for reaction for 2.3 hours, washing by centrifugation, spray drying and grinding to obtain a graphene-silver composite antibacterial agent; S73. According to the mass proportions, 25 parts of graphene-silver composite antibacterial agent are placed into 80 parts of 3-aminopropyltrihydroxysilane solution with a mass concentration of 2%, the temperature is raised to 43°C, and the temperature is kept for 8 hours. The mixture is filtered, washed with ethanol for 3 times, and vacuum dried to obtain a modified graphene-silver composite antibacterial agent.
[0029] Example 1 A method for preparing a high-wiping antistatic dust-free cloth comprises the following steps: S1. Pre-spinning opening: feeding the composite fiber into a bale opener for opening and fine opening, loosening the compressed fiber blocks in the composite fiber into small fiber bundles through mechanical impact and tearing, and then fully mixing in a mixing box to obtain a mixture A, wherein the composite fiber is composed of modified seaweed fiber and ultrafine viscose fiber (the ultrafine viscose fiber has a diameter of 0.5 dtex and a length of 45 mm) in a mass ratio of 1:9; S2, combing and laying: putting the mixed material A into a carding machine for combing, conveying the combed composite fiber to a laying machine for laying, and then forming a fiber cloth through a drafting machine to obtain a fiber cloth; S3, spunlace treatment: conveying the fiber cloth to a spunlace machine and subjecting it to spunlace treatment using 25 MPa high-pressure water to obtain a spunlace cloth; S4, pre-drying: squeeze the spunlace cloth to dry the water, and then send it into the dryer for pre-drying to obtain dust-free cloth; S5. Dip-coating with antibacterial and antistatic liquid: immerse the dust-free cloth in the antibacterial and antistatic liquid, and accurately control the immersion time to be 33 seconds to obtain a dust-free cloth dipped in the antibacterial and antistatic liquid; wherein the antibacterial and antistatic liquid, in terms of weight percentage, is prepared from the following raw materials: 68 parts of methacrylic acid, 0.4 parts of polyvinyl alcohol, 4.5 parts of methacrylamide, 4.5 parts of dimethylaminoethyl acrylate, 3 parts of antistatic agent, 1 part of antibacterial agent, 1 part of surfactant, 3 parts of allyl polyoxyethylene ether, 2.4 parts of initiator aqueous solution, and 395 parts of deionized water; the antibacterial agent is a modified graphene-silver composite antibacterial agent, and the antistatic agent is composed of poly 3,4-ethylenedioxythiophene, octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate, and docosyl trimethyl ammonium chloride in weight percentages. The ratio of 5:3:4 is 5:3:4, the surfactant is composed of octadecyl trimethyl ammonium bromide and polyoxyethylene (10) tridecyl ether in a mass ratio of 4:5, and the initiator aqueous solution is an ammonium persulfate aqueous solution with a mass concentration of 20%; the preparation method of the antibacterial and antistatic liquid is as follows: deionized water and polyvinyl alcohol are added into a glass reaction kettle according to mass fractions, high-purity nitrogen is introduced, and the mixture is stirred at a stirring speed of 300rpm for 1.2h, and then methacrylic acid, methacrylamide, dimethylaminoethyl acrylate, antistatic agent, antibacterial agent, surfactant and allyl polyoxyethylene ether are added in sequence, the temperature is raised to 61°C and kept constant; then the initiator aqueous solution is added to initiate the reaction, the heating is stopped after the reaction for 8h, and the temperature is lowered to room temperature to obtain the antibacterial and antistatic liquid; S6, drying and winding: drying the dust-free cloth dipped in the antibacterial and antistatic liquid at a temperature of 150° C. for 90 seconds, winding it, and cutting it to obtain a highly wiping antistatic dust-free cloth.
[0030] Example 2 A method for preparing a high-wiping antistatic dust-free cloth comprises the following steps: S1. Pre-spinning opening: feeding the composite fiber into a bale opener for opening and fine opening, loosening the compressed fiber blocks in the composite fiber into small fiber bundles through mechanical impact and tearing, and then fully mixing in a mixing box to obtain a mixture A, wherein the composite fiber is composed of modified seaweed fiber and ultrafine viscose fiber (the ultrafine viscose fiber has a diameter of 0.5 dtex and a length of 45 mm) in a mass ratio of 1:9; S2, combing and laying: putting the mixed material A into a carding machine for combing, conveying the combed composite fiber to a laying machine for laying, and then forming a fiber cloth through a drafting machine to obtain a fiber cloth; S3, hydroentanglement treatment: conveying the fiber cloth to a hydroentanglement machine and hydroentanglement treatment with 25 MPa high-pressure water to obtain a hydroentangled cloth; S4, pre-drying: squeeze the spunlace cloth to dry the water, and then send it into the dryer for pre-drying to obtain dust-free cloth; S5. Dip-coating with antibacterial and antistatic liquid: immerse the dust-free cloth in the antibacterial and antistatic liquid, and accurately control the immersion time to be 30 seconds to obtain a dust-free cloth dipped in the antibacterial and antistatic liquid; wherein the antibacterial and antistatic liquid, in terms of mass fractions, is prepared from the following raw materials: 72 parts of methacrylic acid, 0.6 parts of polyvinyl alcohol, 5.5 parts of methacrylamide, 5.5 parts of dimethylaminoethyl acrylate, 5 parts of antistatic agent, 1.2 parts of antibacterial agent, 1.3 parts of surfactant, 5 parts of allyl polyoxyethylene ether, 2.6 parts of initiator aqueous solution, and 400 parts of deionized water; the antibacterial agent is a modified graphene-silver composite antibacterial agent, and the antistatic agent is composed of poly 3,4-ethylenedioxythiophene, octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate and docosyl trimethyl ammonium chloride in mass fractions. The amount ratio is 5:3:4, the surfactant is composed of octadecyl trimethyl ammonium bromide and polyoxyethylene (10) tridecyl ether in a mass ratio of 4:5, and the initiator aqueous solution is an ammonium persulfate aqueous solution with a mass concentration of 20%; the preparation method of the antibacterial and antistatic liquid is: according to the mass ratio, deionized water and polyvinyl alcohol are added to a glass reaction kettle, high-purity nitrogen is introduced, and the stirring is carried out at a stirring speed of 350rpm for 1h, and then methacrylic acid, methacrylamide, dimethylaminoethyl acrylate, antistatic agent, antibacterial agent, surfactant and allyl polyoxyethylene ether are added in sequence, and the temperature is raised to 63°C and kept constant; then the initiator aqueous solution is added to initiate the reaction, and the heating is stopped after the reaction for 9h, and the temperature is lowered to room temperature to obtain the antibacterial and antistatic liquid; S6, drying and winding: drying the dust-free cloth dipped in the antibacterial and antistatic liquid at a temperature of 160° C. for 80 seconds, winding it, and cutting it to obtain a highly wiping antistatic dust-free cloth.
[0031] Example 3 A method for preparing a high-wiping antistatic dust-free cloth comprises the following steps: S1. Pre-spinning opening: feeding the composite fiber into a bale opener for opening and fine opening, loosening the compressed fiber blocks in the composite fiber into small fiber bundles through mechanical impact and tearing, and then fully mixing in a mixing box to obtain a mixture A, wherein the composite fiber is composed of modified seaweed fiber and ultrafine viscose fiber (the ultrafine viscose fiber has a diameter of 0.5 dtex and a length of 45 mm) in a mass ratio of 1:9; S2, combing and laying: putting the mixed material A into a carding machine for combing, conveying the combed composite fiber to a laying machine for laying, and then forming a fiber cloth through a drafting machine to obtain a fiber cloth; S3, hydroentanglement treatment: conveying the fiber cloth to a hydroentanglement machine and hydroentanglement treatment with 25 MPa high-pressure water to obtain a hydroentangled cloth; S4, pre-drying: squeeze the spunlace cloth to dry the water, and then send it into the dryer for pre-drying to obtain dust-free cloth; S5. Dip-coating with antibacterial and antistatic liquid: immerse the dust-free cloth in the antibacterial and antistatic liquid, and accurately control the immersion time to be 32 seconds to obtain a dust-free cloth dipped in the antibacterial and antistatic liquid; wherein the antibacterial and antistatic liquid, in terms of weight percentage, is prepared from the following raw materials: 70 parts of methacrylic acid, 0.5 parts of polyvinyl alcohol, 5 parts of methacrylamide, 5 parts of dimethylaminoethyl acrylate, 4 parts of antistatic agent, 1.1 parts of antibacterial agent, 1.2 parts of surfactant, 4 parts of allyl polyoxyethylene ether, 2.5 parts of initiator aqueous solution, and 398 parts of deionized water; the antibacterial agent is a modified graphene-silver composite antibacterial agent, and the antistatic agent is composed of poly 3,4-ethylenedioxythiophene, octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate, and docosyl trimethyl ammonium chloride in a weight percentage ratio 5:3:4, the surfactant is composed of octadecyltrimethylammonium bromide and polyoxyethylene (10) tridecyl ether in a mass ratio of 4:5, and the initiator aqueous solution is an ammonium persulfate aqueous solution with a mass concentration of 20%; the preparation method of the antibacterial and antistatic liquid is as follows: deionized water and polyvinyl alcohol are added into a glass reaction kettle according to mass fractions, high-purity nitrogen is introduced, and the mixture is stirred at a stirring speed of 330rpm for 1.1h, and then methacrylic acid, methacrylamide, dimethylaminoethyl acrylate, antistatic agent, antibacterial agent, surfactant and allyl polyoxyethylene ether are added in sequence, the temperature is raised to 62°C and kept constant; then the initiator aqueous solution is added to initiate the reaction, the heating is stopped after the reaction for 8.5h, and the temperature is lowered to room temperature to obtain the antibacterial and antistatic liquid; S6, drying and winding: drying the dust-free cloth dipped in the antibacterial and antistatic liquid at a temperature of 155° C. for 85 seconds, winding it, and cutting it to obtain a dust-free cloth with high wiping properties and antistatic properties.
[0032] Comparative Example 1 The same as Example 3, except that an equal amount of seaweed fiber (the diameter of the seaweed fiber is 2.2 dtex and the length is 38 mm) is used instead of the modified seaweed fiber.
[0033] Comparative Example 2 The same as Example 3, except that the antistatic agent is poly 3,4-ethylenedioxythiophene.
[0034] Comparative Example 3 The same as Example 3, except that the antistatic agent is octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate.
[0035] Comparative Example 4 The same as Example 3, except that the antistatic agent is behenyltrimethylammonium chloride.
[0036] Comparative Example 5 The same as Example 3, except that the surfactant is octadecyltrimethylammonium bromide.
[0037] Comparative Example 6 The same as Example 3, except that the surfactant is polyoxyethylene (10) tridecyl ether.
[0038] Performance Testing The high-wiping antistatic dust-free cloths prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were sampled and subjected to the following tests. The test results are shown in Table 1.
[0039] Water absorption test: Cut the non-woven fabric into small pieces of 15mm×150mm, take 100 pieces and weigh a, then put them into a dish filled with distilled water at room temperature and soak for 10 minutes, then take them out and weigh b, water absorption = (ba) / a×100%, measure 5 times and take the average value; Total amount of non-volatile organic compounds (NVR): The extraction solvents used include isopropanol and water. The total weight of non-volatile organic compounds extracted from the non-woven fabric per unit area is tested according to IEST-RP-CC004.2sec.6.1.2; Fiber shedding number: The solvent used is water. According to IEST-RP-CC004.2sec.5.2, the number of shedding fibers with a length greater than or equal to 100μm extracted by water per unit area of non-woven fabric through vibration is tested; The softness test method is as follows: 10 women aged 25-30 are selected to twist the dust-free wipe paper with their hands and score the softness of all samples based on the touch, 1-10 points, the higher the score, the better the softness, and the average of the 10 people is taken; Antistatic performance test: Place the sample at a temperature of 23°C and a relative humidity of 52% for 24 hours. The surface resistivity test refers to the test method in Appendix B of GB / T24249-2009, unit: Ω·m; Antibacterial test: refer to JIS Z2801:2000 standard to conduct antibacterial performance test, and the test object is Escherichia coli.
[0040] Table 1 Performance test Analyzing the data in Table 1, we can see that: 1) The high-wiping antistatic dust-free cloth prepared in Examples 1 to 3 has excellent antibacterial performance, good and durable antistatic performance, high cleanliness, good softness, and is not easy to shed hair and powder, and has high water and oil absorption and excellent ability to clean the surface of objects. At the same time, the preparation method of the present application is simple and efficient, and is suitable for large-scale production.
[0041] 2) The comparative analysis of the performance of the high-wiping antistatic dust-free cloth prepared in Example 3 and Comparative Example 1 shows that the modified seaweed fiber prepared by the present application can improve the thermal stability and spinnability of the seaweed fiber, improve the adhesion and binding force, so that the dust-free cloth has higher water and oil absorption and excellent ability to clean the surface of objects.
[0042] 3) The performance comparison analysis of the high-wiping antistatic dust-free cloth prepared in combination with Example 3 and Comparative Examples 2-4 shows that the antistatic agent is composed of poly 3,4-ethylenedioxythiophene, octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate and docosyl trimethyl ammonium chloride in a mass ratio of 5:3:4. By precisely controlling the mass ratio of poly 3,4-ethylenedioxythiophene, octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate and docosyl trimethyl ammonium chloride, and utilizing the synergistic effect between them, the antistatic retention time and antistatic effect of the high-wiping antistatic dust-free cloth are made more excellent, and it still has a fairly low resistivity even under low humidity conditions. This synergistic effect enables the high-wiping antistatic dust-free cloth to have better performance in practical applications.
[0043] 4) A comparative analysis of the performance of the high-wiping antistatic dust-free cloth prepared in combination with Example 3 and Comparative Examples 5-6 shows that the surfactant is composed of octadecyltrimethylammonium bromide and polyoxyethylene (10) tridecyl ether in a mass ratio of 4:5. The synergistic effect between octadecyltrimethylammonium bromide and polyoxyethylene (10) tridecyl ether can improve the wettability, emulsification and permeability of the antibacterial and antistatic liquid, making it easier to penetrate into the non-woven fabric and form a stable emulsion structure, thereby improving the comprehensive performance of the high-wiping antistatic dust-free cloth.
[0044] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the scope of protection of the present application.
Claims
1. A method for preparing a highly wiping antistatic dust-free cloth, It is characterized in that The following steps are involved: S1. Pre-spinning opening: feeding the composite fiber into a bale opener for opening and fine opening, so that the compacted fiber blocks in the composite fiber are loosened into small fiber bundles through mechanical impact and tearing, and then fully mixed in a mixing box to obtain a mixture A; S2, combing and laying: putting the mixed material A into a carding machine for combing, conveying the combed composite fiber to a laying machine for laying, and then forming a fiber cloth through a drafting machine to obtain a fiber cloth; S3, spunlace treatment: conveying the fiber cloth to a spunlace machine and subjecting it to spunlace treatment using 25 MPa high-pressure water to obtain a spunlace cloth; S4, pre-drying: squeeze the spunlace cloth to dry the water, and then send it into the dryer for pre-drying to obtain dust-free cloth; S5, dip-coating with antibacterial and antistatic liquid: immerse the dust-free cloth in the antibacterial and antistatic liquid, accurately control the immersion time to be 30-33 seconds, and obtain the dust-free cloth dipped in the antibacterial and antistatic liquid; wherein, the antibacterial and antistatic liquid, in terms of weight parts, is prepared from the following raw materials: 68-72 parts of methacrylic acid, 0.4-0.6 parts of polyvinyl alcohol, 4.5-5.5 parts of methacrylamide, 4.5-5.5 parts of dimethylaminoethyl acrylate, 3-5 parts of antistatic agent, 1-1.2 parts of antibacterial agent, 1-1.3 parts of surfactant, 3-5 parts of allyl polyoxyethylene ether, 2.4-2.6 parts of initiator aqueous solution, and 395-400 parts of deionized water; S6, drying and winding: drying the dust-free cloth dipped in the antibacterial and antistatic liquid at a temperature of 150-160° C. for 80-90 seconds, winding it, and cutting it to obtain a highly wiping antistatic dust-free cloth; The composite fiber is composed of modified seaweed fiber and ultrafine viscose fiber in a mass ratio of 1:
9.
2. A method for preparing a highly wiping antistatic dust-free cloth according to claim 1, It is characterized in that The modified seaweed fiber has a diameter of 2.2 dtex and a length of 38 mm; the ultrafine viscose fiber has a diameter of 0.5 dtex and a length of 45 mm.
3. A method for preparing a highly wiping antistatic dust-free cloth according to claim 1, It is characterized in that The preparation method of the modified seaweed fiber is as follows: treating the seaweed fiber with oxygen plasma at a temperature of 35° C., a vacuum degree of 1000 Pa, and a plasma power supply of 500 W, then immersing the seaweed fiber in nano-silica sol, adding 1.2% of dodecyltrimethylammonium bromide based on the mass of the seaweed fiber, treating for 2-3 hours, then adding 5-7% of hexachloropropane based on the mass of the seaweed fiber, stirring evenly, washing with deionized water, and drying to obtain the modified seaweed fiber.
4. A method for preparing a highly wiping antistatic dust-free cloth according to claim 3, It is characterized in that The mass ratio of the seaweed fiber to the nano-silicon dioxide sol is 5:17-20.
5. A method for preparing a highly wiping antistatic dust-free cloth according to claim 1, It is characterized in that In step S5, the antistatic agent is composed of poly (3,4-ethylenedioxythiophene), octadecyldimethylhydroxyethyl quaternary ammonium nitrate and behenyltrimethylammonium chloride in a mass ratio of 5:3:
4.
6. A method for preparing a highly wiping antistatic dust-free cloth according to claim 1, It is characterized in that In step S5, the antibacterial agent is a modified graphene-silver composite antibacterial agent.
7. A method for preparing a highly wiping antistatic dust-free cloth according to claim 6, It is characterized in that The preparation method of the modified graphene-silver composite antibacterial agent comprises the following steps: S71. According to the mass fraction, 30 parts of 30 μm thick flake graphite and 200 parts of anhydrous ethanol were mixed, and the solution was mixed evenly by using a variable frequency disperser, and then the mixed solution was poured into a high temperature and high pressure reactor, and the temperature was set to 310°C, the pressure was controlled at 30 MPa, and the speed was 900 r / min. After keeping warm for 40 minutes, the equipment was turned off, the pressure relief valve was opened, and the solution was placed in deionized water at room temperature. When the pressure dropped to 15 MPa, the pressure relief valve was closed, and the product was subjected to ultrasonication, washing, and suction filtration to obtain a filter cake, and the filter cake was freeze-dried for 24 hours and then taken out to obtain graphene; S72, dissolving 25 parts of graphene, 5 parts of silver nitrate and 0.5 parts of sodium hydroxide in 800 parts of deionized water respectively according to their weight parts, stirring evenly, heating to 92° C., keeping the temperature for reaction for 2h-2.5h, washing by centrifugation, spray drying and grinding to obtain a graphene-silver composite antibacterial agent; S73. According to the mass proportions, 25 parts of graphene-silver composite antibacterial agent are placed into 80 parts of 3-aminopropyltrihydroxysilane solution with a mass concentration of 2%, the temperature is raised to 43°C, kept warm for 8 hours, filtered, washed with ethanol 3 times, and vacuum dried to obtain a modified graphene-silver composite antibacterial agent.
8. A method for preparing a highly wiping antistatic dust-free cloth according to claim 1, It is characterized in that In step S5, the surfactant is composed of octadecyltrimethylammonium bromide and polyoxyethylene (10) tridecyl ether in a mass ratio of 4:
5.
9. A method for preparing a highly wiping antistatic dust-free cloth according to claim 1, It is characterized in that In step S5, the mass concentration of the initiator aqueous solution is 20%, and the initiator is ammonium persulfate.
10. A highly wiping antistatic dust-free cloth, It is characterized in that The high-wiping antistatic dust-free cloth is prepared by the preparation method of any one of claims 1 to 9.
